Shell-model study of weak β-decays relevant to astrophysical processes - Suzuki, Toshio; Shimizu, Noritaka (Frontiers in Physics, 2024)
Shell-model studies on the weak β-decay in nuclei relevant to astrophysical processes are carried out. The β-decay rates, as well as electron-capture rates in sd-pf shell induced by Gamow-Teller (GT) transition, are evaluated in astrophysical environments. The weak rates for the nuclear Urca pair of nuclei with A=31 in the island of inversion, which are important for the nuclear Urca processes in neutron star crusts, are investigated by shell-model calculations in the sd-pf shell. The GT strength is evaluated in sd-pf shell for selected β-decays in the sd-shell nuclei, and the effects of the expansion of the configuration space on the quenching of the axial-vector coupling are examined. β-decay rates induced by first-forbidden (FF) transitions are studied by the Behrens-B ühring (BB) method for the isotones with N =126, and compared with the Walecka method. The important role of the electron distortions in the β-decays of 206 Hg and 207 Tl is pointed out.